2022
DOI: 10.3390/resources11010006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Terrestrial Evaporation across Poland over the Past Four Decades Dominated by Increases in Summer Months

Abstract: Given the importance of terrestrial evaporation (ET) for the water cycle, a fundamental understanding of the water quantity involved in this process is required. As recent observations reveal a widespread ET intensification across the world, it is important to evaluate regional ET variability. The specific objectives of this study are the following: (1) to assess annual and monthly ET trends across Poland, and (2) to reveal seasons and regions with significant ET changes. This study uses the ET estimates acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The frequency of the occurrence of low stratiform clouds has clearly decreased in the last two decades in Poland (Matuszko et al 2022), which translated into significant increases in sunshine duration in the spring and summer seasons (Bartoszek et al 2020). As a result, the increased net solar flux at the surface contributed to the increase in evapotranspiration, as well as the reduction of water resources in soil in the research area (Somorowska, 2022). In turn, stronger heating of the ground is often conducive to the formation of a greater number of heavy vertical convective clouds, which are characterised by short-term but intense precipitation (Luo et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the occurrence of low stratiform clouds has clearly decreased in the last two decades in Poland (Matuszko et al 2022), which translated into significant increases in sunshine duration in the spring and summer seasons (Bartoszek et al 2020). As a result, the increased net solar flux at the surface contributed to the increase in evapotranspiration, as well as the reduction of water resources in soil in the research area (Somorowska, 2022). In turn, stronger heating of the ground is often conducive to the formation of a greater number of heavy vertical convective clouds, which are characterised by short-term but intense precipitation (Luo et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Somorowska [13] evaluated the trends in terrestrial evaporation (ET) across Poland using data from 1980 to 2020. The study aimed to assess annual and monthly ET trends and revealed significant changes of this variable over different seasons and regions.…”
Section: Water Resource Monitoring and Modelling Insights From The Pu...mentioning
confidence: 99%
“…The temperature rise in summer and autumn is more moderate (0.15-0.25°C/10 years). Rising temperatures cause an increase in potential evapotranspiration (PET) (Bogawski and Bednorz, 2016;Nistor et al, 2022;Somorowska, 2022a;Teuling et al, 2009), which in turn contributes to a decrease in soil moisture content, a reduction of groundwater recharge, and lower groundwater levels. Several significant droughts occurred in Europe in the last years (e.g., Bastos et al, 2020;Christian et al, 2020;Garcia-Herrera et al, 2010;García-Herrera et al, 2019;Grillakis, M. G., 2019;Ionita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%